2019
DOI: 10.1029/2019jg005255
|View full text |Cite
|
Sign up to set email alerts
|

Stable Carbon and Oxygen Isotopes in Shell Carbonates of modern Land Snails in China and Their Relation to Environment Variables

Abstract: Stable isotopes of land snail fossil shell carbonates (δ 13 C shell and δ 18 O shell ) provide the opportunity to decipher paleodietary and paleoenvironmental changes. However, the environmental meanings of δ 13 C shell and δ 18 O shell remain elusive especially in the monsoonal climate region. To elucidate this, δ 13 C shell and δ 18 O shell of the two most common land snails in China, Cathaica and Bradybaena, were analyzed in this study. Results show that Bradybaena has a wider distribution than Cathaica and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…From June to September, the δ 18 O of precipitation demonstrates a clear drop (i.e., down to −7.9‰ in July) due to the large rainfall amount (Figure 1 from Wang et al., 2016). This result is consistent with the amount effect on rainfall δ 18 O in monsoonal regions (e.g., Dansgaard, 1964; Wang et al., 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From June to September, the δ 18 O of precipitation demonstrates a clear drop (i.e., down to −7.9‰ in July) due to the large rainfall amount (Figure 1 from Wang et al., 2016). This result is consistent with the amount effect on rainfall δ 18 O in monsoonal regions (e.g., Dansgaard, 1964; Wang et al., 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Land snail fossils are abundant and widely distributed in the Asian monsoon region, especially in the Chinese Loess Plateau (Gu et al, 2009;Liu et al, 2006;Wu et al, 1996Wu et al, , 2002. However, research on the stable isotopes of snail shells has mainly focused on studying modern land snails in different climatic regions (Bao et al, 2018(Bao et al, , 2019Liu et al, 2006;Wang et al, 2016Wang et al, , 2019Zhai et al, 2019). In contrast, stable isotope analyses of fossil snails in sedimentary successions have been inadequately performed, and only a few species of land snails have been studied (Gu et al, 2009;Huang et al, 2012).…”
mentioning
confidence: 99%
“…This is supported by several other studies from the monsoon regions of China. For example, Wang et al (2019) found that δ 13 Cshell in Bradybaena snails throughout China reflects the δ 13 C of regional C3 plants controlled by rainfall amount, confirming the use of δ 13 Cshell as a precipitation proxy.…”
Section: Background: Climatic Significance Of Snail δ 13 Cshell In Th...mentioning
confidence: 76%
“…Thus, it is generally agreed that the δ 13 C of the plant material ingested by a snail is the dominant control on δ 13 Cshell, which in turn reflects the regional vegetation composition (i.e., C3, C4, and CAM) (e.g., Balakrishnan et al, 2005;Stott, 2002), and thus the humidity of the local environment (Prendergast et al, 2017;Yanes et al, 2009). However, δ 13 Cshell can also be influenced by a snail's environmental carbonate ingestion, atmospheric CO2, and several eco-physiologicallyrelated factors (i.e., food preference, metabolic rates, and the duration of activity), resulting in a regionally specific relationship between δ 13 Cshell and environmental variables (Balakrishnan, M., and Yapp, 2004;Bao et al, 2018;Goodfriend and Ellis, 2002;Wang et al, 2019). Therefore, it is necessary to evaluate the climatic significance of δ 13 Cshell in the EASM region before using it for paleoclimatic reconstruction.…”
Section: Background: Climatic Significance Of Snail δ 13 Cshell In Th...mentioning
confidence: 99%
“…Due to differences in metabolic pathways, C4 plants (e.g. tropical grass) typically have a higher δ 13 C than C3 plants and therefore higher δ 13 C shell values are interpreted to reflect higher relative C4 plant intake when the snail's diet is mixed (Balakrishnan and Yapp, 2004; Wang et al, 2019). In non‐tropical settings and situations where the diet of the snail does not include C4 plants, differences in δ 13 C shell can reflect differences in water use efficiency of the plants ingested by the snail (Diefendorf et al, 2010; Tibby et al, 2016).…”
Section: Introductionmentioning
confidence: 99%